Identifikasi Elemen dan Pola Ruang pada Taman Vihara Dharma Giri di Kecamatan Pupuan, Kabupaten Tabanan, Bali - Tantowi, Benny; Sugianthara, Anak Agung Gede; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023DO - 10.24843/JAL.2023.v09.i01.p08, 2023)
Identification of Elements and Spatial Patterns in the Dharma Giri Monastery Park in Pupuan District, Tabanan Regency, Bali. This research is motivated by the absence of a description of the spatial pattern used and the character of the forming elements at Vihara Dharma Giri in Pupuan District, Tabanan Regency, Bali. This study aims to identify the physical conditions, elements and patterns of space and the philosophical concept of the Vihara Dharma Giri Garden. The method used in this research is a survey method with data collection techniques by means of observation, interviews, and literature study as well as descrictive qualitative data analysis. The results of data analysis are presented in the form of an illustration of the Dharma Giri Vihara space pattern. Based on the analysis, it is found that the characters are based on the Vihara Dharma Giri by the biophysical aspects and have a spatial pattern that follows the Tri Hita Karana concept. In the division of space, there is also a garden area which is also called a statue garden. The role and elements of society are needed in maintaining and caring for the Vihara Dharma Giri so that its sustainability is maintained.   Keywords: Dharma Giri Monastery, Identification, Landscape-forming Elements, Spatial Patterns